Najrān in the Sīra: narrative roles and Muslim attitudes towards the South Arabian Christians - Løvlund Toft, Lasse (Semitica et Classica, 2021)
Abstract The biography of Muḥammad compiled by Ibn Isḥāq (d. 767) and later written out by Ibn Hišām (d. 834) into the Sīrat Rasūl Allāh is the most important testimony to early Muslims’ pious representations of their Prophet. In it, the Christian community in the South Arabian city of Najrān plays a small but significant role throughout the whole narrative as pre- Islamic monotheists, as zealous and stubborn representatives of Christianity in religious debates, and even as acknowledgers of Islam. Through textual analyses of five sections in the Sīra, this article investigates the narrative roles, that the Christian community in Najrān plays in the Sīra and how this peripheral religious group is viewed by the Muslim compilers. It argues that the stories of the Christianization of Najrān are included in order to frame and give context to the Sīra’s later narratives on the interactions between the Christians and the Muslim community in Medina, and that the Christians of Najrān serve as representatives for Christianity as a whole. At the end of the article, an appendix is included with an annotated close textual and narrative comparison between the Sīra’s story of Faymiyūn and Ṣāliḥ and a Syriac hagiographical work from the 5th century about Paul of Qenṭos and John of Edessa, which likely was the Sīra’s source. Abstract Compilée par Ibn Isḥāq (m. 767) avant d’être rédigée par Ibn Hišām (m. 834) sous le titre de Sīrat Rasūl Allāh, la biographie de Muḥammad est un témoignage exceptionnel des premières représentations que les musulmans se faisaient de leur Prophète. Tout au long du texte, la communauté chrétienne de Najrān - ville du sud de l’Arabie - joue un rôle modeste et pourtant significatif, car elle y incarne tout à la fois le monothéisme préislamique, un christianisme affirmé et zélé au moment des débats religieux et même une forme de reconnaissance de l’islam. À partir d’une analyse textuelle de cinq sections de la Sīra, cet article étudie le rôle que joue la communauté chrétienne de Najrān dans le programme narratif du texte et reconstitue la manière dont ce groupe religieux périphérique fut perçu par les premiers compilateurs musulmans. Il démontre ainsi que les histoires de la christianisation de Najrān ont été insérées par l’auteur de la Sīra afin de donner un contexte à d’autres récits relatifs aux chrétiens, notamment celui des interactions entre les chrétiens et la communauté musulmane de Médine. Plus généralement, les chrétiens de Najrān incarnaient dans la Sīra le christianisme dans son ensemble. L’article comprend aussi, en annexe, une comparaison textuelle détaillée de deux récits proches : celui de Faymiyūn et Ṣāliḥ tiré de la Sīra et celui de Paul de Qenṭos et Jean d’Édesse - une oeuvre hagiographique syriaque du ve s. - qui a probablement constitué la source du premier.